Juvenile Delinquency - Factors and Treatments in Iraqi Legislation - Osman Mustafa Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
this study is concerned with the analytical descriptive approach, by talking about the adequacy of the protection of the Iraqi legal system, especially the Juvenile Welfare Law No. 76 of 1983, for the phenomenon of juvenile delinquency? In view of the great development witnessed by the human society and the Iraqi society in the field of the emergence of information and communication technology and various other fields that help in the increase of criminal behavior such as violence, terrorism, theft and sexual crimes among juveniles. As well as the effectiveness of those laws to reform juveniles? And the extent of their effectiveness in rehabilitating operations to put an end to juvenile delinquency? After it has become scientifically proven that the means of violence and punishment are useless as a way to treat juvenile delinquency, but rather it increases its complexity. The research methodology required that it be divided into: an introduction, three topics, and a conclusion: The first topic was devoted to talking about the concept of juvenile and the seriousness of juvenile delinquency, and we will shed light on the seriousness of juvenile delinquency by showing the negative effects of delinquency on the juveniles themselves and on society. In the second topic, the focus is on the factors affecting juvenile delinquency through the internal and external factors of juvenile delinquency. As for the third topic, it is devoted to studying the preventive and therapeutic aspects of juvenile delinquency. In the conclusion, a number of conclusions and recommendations that have been reached are presented in the light of the problems raised through this study